1988
DOI: 10.1177/36.11.2844888
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal gold immunostaining on deplasticized ultra-thin sections.

Abstract: We localized tissue antigens on ultra-thin sections by deplasticizing the sections while on the grid, incubating in primary antiserum followed by immunoglobulin-conjugated colloidal gold, and ultimately re-embedding in dilute Epon. This procedure permitted ultrastructural localization of tissue antigens that were previously masked by the embedding plastic surrounding tissue components. In addition, replacement ofthe plastic matrix on the thin section after immunostaining prevented development ofthe drying arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Similarly, Brorson (1997) demonstrated that the immunoreactivity of most antigens is not affected by sodium ethoxide treatment, as ultrathin sections prepared from specimens fixed with formaldehyde and embedded in LR-White, a sodium ethoxide resistant resin, showed no significant difference in immunostaining after sodium ethoxide treatment. Mar and Wight (1988) reported similar results using epon-embedded tissues fixed with a formaldehyde and glutaraldehyde mixture. Whether the great reduction in PCNA-immunostaining by sodium ethoxide treatment is due to the direct modification of the PCNA epitope by ethoxide or the extraction of PCNA because of the destruction of crosslinks between PCNA and neighboring nuclear proteins remains unclear.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, Brorson (1997) demonstrated that the immunoreactivity of most antigens is not affected by sodium ethoxide treatment, as ultrathin sections prepared from specimens fixed with formaldehyde and embedded in LR-White, a sodium ethoxide resistant resin, showed no significant difference in immunostaining after sodium ethoxide treatment. Mar and Wight (1988) reported similar results using epon-embedded tissues fixed with a formaldehyde and glutaraldehyde mixture. Whether the great reduction in PCNA-immunostaining by sodium ethoxide treatment is due to the direct modification of the PCNA epitope by ethoxide or the extraction of PCNA because of the destruction of crosslinks between PCNA and neighboring nuclear proteins remains unclear.…”
Section: Discussionsupporting
confidence: 68%
“…Collagen fibrils present in the adventitia of arterioles in the brain parenchyma ( Figure 2E) also demonstrated positive immunogold labeling of decorin ( Figure 2F). The association of decorin with collagen indicated that the antibody was active and effectively localized to collagen, as others have demonstrated ( Mar and Wight, 1988;Scott and Haigh, 1985;Young, 1985;Scott and Orford, 1981).…”
Section: Nf?s (supporting
confidence: 59%
“…After fixation, tissue fragments were washed in phosphate buffer, dehydrated through graded alcohols and embedded in Spurr's resin. Semi-thin sections (1.5/~m) were deplasticized using a solution of saturated NaOH in absolute ethanol (sodium ethoxide) for 30 min at room temperature and then processed for immunocytochemical staining [ 16]. Deplasticized sections were immersed in 0.3~o H202 in PBS for 30 min in order to abolish endogenous peroxidase activity.…”
Section: Immunocytolocalization Of Glyoxalase-imentioning
confidence: 99%